PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH CV. BERKAH JAYA GENERAL SUPPLIER SNACK FOOD - Yaya Suharya; Sutrisno Sutrisno; Risma Nurmilah (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2021)
In addition to providing goods and services, the company aims to obtain maximumprofit. As a provider of goods, the fulfillment of better product quality and competitiveprices is a challenge for the company. However, this was accompanied by highproduction costs. Thus, companies are required to be able to reduce production costswhich consist of raw material costs, direct labor wages and factory overhead. Theabove phenomenon inspires the author to examine